A microbial biomanufacturing platform for natural and semi-synthetic opiates - Thodey, Kate (2014)
Opiates and related molecules are medically essential, but their production via field cultivation of opium poppy Papaver somniferum leads to supply inefficiencies and insecurity. As an alternative production strategy, we developed baker's yeast Saccharomyces cerevisiae as a microbial host for the transformation of opiates. Yeast strains engineered to express heterologous genes from P. somniferum and bacterium Pseudomonas putida M10 convert thebaine to codeine, morphine, hydromorphone, hydrocodone, and oxycodone. A new biosynthetic branch to neopine and neomorphine was discovered, which diverted pathway flux from morphine and other target products. Strain titer and specificity was optimized by titrating gene copy number, enhancing cosubstrate supply, applying a spatial engineering strategy, and performing high-density fermentation, resulting in total opioid titers up to 131 mg/L. This work is an important step toward total biosynthesis of valuable benzylisoquinoline alkaloid drug molecules and demonstrates the potential for developing a sustainable and secure yeast biomanufacturing platform for opioids.